2014
DOI: 10.1021/jp5053024
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Transformation of Carboxyl Groups on the Surface of Silicon Carbide Quantum Dots

Abstract: Silicon carbide quantum dots in the size range of 1-10 nm are in the center of interest with unique properties that makes them very promising biomarkers. A central requirement for this application is the control over the complex structure of the surface to enable further surface functionalization processes, which are crucial for drug delivery.In this paper a temperature dependent infrared and photoluminescence spectroscopy study, combined with ab initio modeling, is presented in order to reveal the chemical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…is practically explored in our work for the first time. Indeed, formation of "carbon-enriched layers" on the HF-etched SiC surface was observed before 11,35 and closely studied recently 36,37 , however, exact composition of a colored soluble etching products was, on our knowledge, not characterized up to now.…”
Section: Discussionmentioning
confidence: 83%
“…is practically explored in our work for the first time. Indeed, formation of "carbon-enriched layers" on the HF-etched SiC surface was observed before 11,35 and closely studied recently 36,37 , however, exact composition of a colored soluble etching products was, on our knowledge, not characterized up to now.…”
Section: Discussionmentioning
confidence: 83%
“…NCs of diameter between 1-4 nm were terminated with a variety of oxygen-containing species with high concentration of carboxyl groups 15 that we label by 'as-prepared'. We prepared -OH, -H and -SiO x ter- prepared sample shows a strong and broad peak at around 3300 cm -1 because of the strongly hydrogenbonded OH groups on the surface and hydrogen-bonded water molecules 15 .…”
Section: Synthesis Of Different Surface Terminated Sic Ncsmentioning
confidence: 99%
“…15,17,21 The details about the methodology are given in the SI. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 the nanocrystals, respectively) iv) majority of the hydrogen atoms substituted with -OH groups on both the silicon-and carbon-terminated faces of the nanocrystal, the remaining hydrogen atoms substituted with -COO -Na + moieties; v) hydrogen atoms substituted with -OH groups on the silicon terminated surface while the carbon atoms on the originally carbon terminated surface were substituted with oxygen atoms to form a thin SiO 2 layer.…”
Section: Ab Initio Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also exhibits great application potential in ultraviolet (UV) photodiodes 4 , spintronics 5, 6 and quantum information processing 7,8,9 . Experimental results 24,25 and theoretical calculations showed that the luminescence of SiC NCs is strongly influenced by the surface groups 26 . These polytypes are identical in two dimensions (hexagonal basal plane) and differ in the Si-C bilayer sequences in the third dimension (c-axis perpendicular to the basal plane) 10 .…”
mentioning
confidence: 99%